Personal hygiene: prerequisite to healthy living in schools (2014)
This article critically examines literature and empirical studies on personal hygiene and as a fundamental factor for healthy living in schools. Its main focus is on the basic concept of cleaning, grooming, caring for the body and efforts at making the body look good and attractive. The paper also looked at the roles of schools in providing sanitation facilities that will promote personal hygiene. While there is no doubt about the importance of personal hygiene to healthy living, the review revealed a poor state of personal hygiene and its effect on the health of school children. The article also shows that there are still major economic, educational, environmental, social and personal barriers to the practice of personal hygiene among Nigerian school children. The concluding part considered the importance of health education in the future of personal hygiene practices in relation to healthy school living. It recommended that health education should be used as a potent force to instil health literacy needed to predispose school children to hygienic practices.